2017
DOI: 10.1590/1414-431x20176613
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in the APOB gene and hyperlipidemia in the Chinese Yugur population

Abstract: We investigated the influence of apolipoprotein B gene (APOB) variants on the risk of hyperlipidemia (HL) in 631 middle-aged and elderly members of the Chinese Yugur population (HL, n=336; normolipidemia, n=295). APOB polymorphisms were identified using mass spectrometry, and five single nucleotide polymorphisms (rs1042034, rs2163204, rs512535, rs676210, and rs679899) and serum lipids were further analyzed. rs1042034 and rs676210 were significantly associated with HL (P<0.05). Compared with the GG or AA genoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
(30 reference statements)
2
22
0
Order By: Relevance
“…p.12_15del is associated with higher levels of apoB and LDL cholesterol without affecting triglyceride levels 36,37) . p.N2785H has no effect on hyperlipidemia risk in the Chinese population 37) . No diseasecausing variants were detected in the apo B gene.…”
Section: Discussionmentioning
confidence: 99%
“…p.12_15del is associated with higher levels of apoB and LDL cholesterol without affecting triglyceride levels 36,37) . p.N2785H has no effect on hyperlipidemia risk in the Chinese population 37) . No diseasecausing variants were detected in the apo B gene.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Studies have confirmed that multiple singlenucleotide polymorphisms (SNPs) in APOB are associated with dyslipidemia. 10,11 China is a multiethnic country comprising Han Chinese, which accounts for the majority, and 55 ethnic minorities. The Maonan ethnic group is one of the ethnic minorities living in the mountainous region, which has a small population.…”
Section: Introductionmentioning
confidence: 99%
“…APOB is considered the third most relevant candidate modifier gene for MEND syndrome because up to seven of its allelic variants have been reported to be significantly associated with increased levels of LDL‐C or hyperlipidemia. Among these variants, p.Ala618Val (rs679899) (Gu et al, ) and p.Ile408Thr (rs12714225) (Teslovich et al, ) were the fourth and fifth top variants in Table , respectively. The presence of p.Ala618Val in compound heterozygosity with p.Ile408Thr in Patients 1, 2, and 3 and the absence of both in Patient 4, who had the mildest MEND phenotype, supports its contribution to the genotype–phenotype association in MEND syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all patients with MEND syndrome appear to have a basal deficiency in APOB function because they carry APOB alleles carrying ancestral sequences of the SNPs rs1042034 and rs676210. These SNPs are hypothesized to predispose middle‐aged and elderly members of the Chinese Yugur population to hyperlipidemia in combination with other genetic or nutritional factors (Gu et al, ). Patient 2 and especially Patient 3 may exhibit somewhat higher degrees of deficiency in the synthesis of lipoproteins because of the presence of compound heterozygosity for potentially functional APOB alleles.…”
Section: Discussionmentioning
confidence: 99%